Quem o direito protege? Uma análise interseccional sobre a tipificação de casos de feminicídios no Estado da Paraíba - Pereira, Jaíne Araújo (2021)
Law 13.104 amended, in 2015, the Brazilian Penal Code and brought a new qualifier for the crime of homicide. In this context, femicide can be defined as the crime committed against women motivated because of “the condition of women”; thus, it is the final stage of the violence to which women are victims. In this scenario, this research aims to analyze the use of the femicide qualifier based on an examination of the application of justice in six concrete cases in the State of Paraíba. The specific objectives, in turn, are to situate women in Brazilian society; to study the institution of the femicide qualifier in Brazil; to examine whether the typification of femicide is being underreported through concrete case studies, and to explore the consequences of underreporting femicide cases in the State mentioned above. The research sites were: João Pessoa-PB, Campina Grande-PB, and Mamanguape-PB, and bodies and institutions linked to the data processing on the femicide qualifier, such as the Secretariat of Security and Social Defense and the Civil Police, both from the State of Paraíba. The importance of the study is justified by the fact that most existing research on the subject is only concerned with defining theoretical aspects of the issue. Additionally, the present work also intends to observe whether the qualifier is being employed in the State of Paraíba. The research still holds social relevance, considering that the analyses can function as a thermometer to create new public policies in defense of women's lives. Furthermore, the inductive approach method and the method of monographic style procedure were employed; the research level, in turn, is exploratory and refers to a study that involves a bibliographic-documentary survey. Thus, indirect documentation was used to collect data on femicide and violence against women and direct documentation for field research. Likewise, a bibliographical and documentary review on the subject was carried out based on the works of Saffiotti (2013 and 2015), Carneiro (2011), Gonzales (1984), among others. Then, it was investigated, based on the same documents that the authorities had access for assistance in the cases' typification, whether the crimes should be classified as femicide. The study points to the importance of proper systematization of data on extreme violence cases against women, as all cases of femicide in the sample are listed simply as “homicide” in the public procedure query of the Court of Justice of Paraíba. Such procedural turmoil hinders data collection and makes it difficult to create public policies to fight gender violence, as it is necessary to know accurately the number, the places, and the way women are dying due to gender inequality. This proves that it is methodologically risky to carry out an investigation based only on electronic data obtained from the computer systems of public agencies. It is necessary to consult the body of the proceedings and verify all pages of the records if it is a case of femicide.